Konservasi Hutan Adat melalui Pendekatan Budaya: Perspektif Masyarakat Wetu Telu Bayan, Lombok Utara - Bambang Patmaraga; Muhammad Sarjan (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Customary forests in Bayan, North Lombok, are managed by the Wetu Telu com-munity through a value system that blends religious belief, cosmology, and local wisdom, making forest sustainability inseparable from the cultural dimension of the community that safeguards it. This study aims to map and synthesize prior scholarly findings on the conservation of Bayan's customary forest from a cultural perspective, focusing on the values underlying conservation practices, the custom-ary rules applied, the roles of various socio-cultural actors, and the challenges that emerge amid modernization. The study was conducted through a Systematic Liter-ature Review (SLR) approach, in which relevant prior publications on Wetu Telu customary forest conservation were searched, screened, and analyzed to identify recurring patterns and connecting threads across studies. The findings show that the syncretism between Islamic values and local tradition shapes a view of the for-est as sacred space, which is then institutionalized through the awig-awig custom-ary rules as a mechanism of social control over forest resource use. The effectiveness of forest conservation is further shaped by the roles of customary leaders, religious figures, families, and collaboration with village governments, although its continui-ty faces pressure from shifting values among younger generations and inconsisten-cies between customary law and national law. This culture-based conservation is shown to generate multidimensional benefits, contributing to ecological sustaina-bility, economic value, and social cohesion within the community. These findings affirm that the preservation of Bayan's customary forest should be understood as an ongoing socio-cultural process, suggesting that future environmental governance policies should position indigenous communities as primary partners rather than mere objects of regulation.